Eksplorasi Kue Tradisional Batak Toba Terhadap Konsep Geometri - Tutiarny Naibaho; Samuel Juliardi Sinaga; Venny Herawati Simangunsong; Susi Sihombing (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT The purpose of the research conducted by the author is to dig deeper into the ethnomathematics of traditional Batak cakes on the concept of geometry. This research is a qualitative research with an ethnographic approach. The results of this study indicate that there is an ethnomathematical element in traditional Batak cakes, namely the concept of geometry and can be used as a learning medium. In conclusion, the five traditional cakes have a geometric concept, namely the concept of building space which is found including rectangular pyramids on rice lapet; balls on gadong cake; rectangular prism on the Labar; arbitrary prism at nitak; and cones on lapet pulut and ombus-ombus. Keywords: Ethnomathematics, Learning Media, Geometry, Traditional Cakes, Batak.